CellTracksColab is a platform that enables compilation, analysis, and exploration of cell tracking data - Gómez-de-Mariscal, Estibaliz; Grobe, Hanna; Pylvänäinen, Joanna W.; Xénard, Laura; Henriques, Ricardo; Tinevez, Jean-Yves; Jacquemet, Guillaume (PUBLIC LIBRARY SCIENCE, 2025)
In life sciences, tracking objects from movies enables researchers to quantify the behavior of single particles, organelles, bacteria, cells, and even whole animals. While numerous tools now allow automated tracking from video, a significant challenge persists in compiling, analyzing, and exploring the large datasets generated by these approaches. Here, we introduce CellTracksColab, a platform tailored to simplify the exploration and analysis of cell tracking data. CellTracksColab facilitates the compiling and analysis of results across multiple fields of view, conditions, and repeats, ensuring a holistic dataset overview. CellTracksColab also harnesses the power of high-dimensional data reduction and clustering, enabling researchers to identify distinct behavioral patterns and trends without bias. Finally, CellTracksColab also includes specialized analysis modules enabling spatial analyses (clustering, proximity to specific regions of interest). We demonstrate CellTracksColab capabilities with 3 use cases, including T cells and cancer cell migration, as well as filopodia dynamics. CellTracksColab is available for the broader scientific community at https://github.com/CellMigrationLab/CellTracksColab.Exploring large amounts of cell tracking data remains a challenge. This study presents CellTracksColab, a platform that provides a transformative solution for cell tracking analysis, combining cutting-edge computational methods with a user-friendly interface.